Transformasi Bisnis Sebagai Wahana Ibadah Dan Muamalah Dalam Perspektif Ekonomi Islam - Wahyuddin, Wahyuddin; Amir, A. M. Nur Atma; Muin, Rahmawati (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
Business is an important aspect of human life as a means of fulfilling economic needs. However, in an Islamic perspective, business is not only seen as a profit-seeking activity, but also as a field of worship that is worth muamalah. This concept integrates economic and spiritual aspects, where every business activity carried out with good intentions and the right way will be worth worship in the sight of Allah SWT. This research aims to find out Business as a Field of Worship charity and to find out the behaviour of business people in Islam. This research method uses library research methods or library research. The results showed that business is not only seen as an economic activity, but also can be a land of worship full of blessings. This concept is based on the principle that all activities carried out with good intentions, the right way according to Islamic law, and produce benefits for others can be a means of charity and worship to Allah.